2014
DOI: 10.7202/1025563ar
|View full text |Cite
|
Sign up to set email alerts
|

Autoépuration en eau courante : évaluation de l’oxygénation dans les cascades en marches d’escalier

Abstract: Dans les écosystèmes aquatiques, l’oxygène dissous est consommé par les processus chimiques et biologiques de l’autoépuration (oxydoréduction, dégradation de la matière organique,...) ainsi que par la respiration des espèces aquatiques. L’autoépuration sera donc favorisée par une amélioration de l’aération et le taux d’oxygène dissous constituera un indicateur de la qualité de l’eau. Les structures hydrauliques telles que les cascades jouent le rôle de système d’aération en favorisant l’absorption dans l'eau d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…During the study, the natural regeneration of the sand deposit during large flood events was observed. It is possible to improve the system by replacing the artificial weirs with ramps of gabions 2 that maintain hydraulic continuity and produce more efficient aeration than waterfalls (Khdhiri 2014;Khdhiri et al 2014). Constructed riffles should be tested on other small creeks in parallel with a design assistance model.…”
Section: Discussionmentioning
confidence: 99%
“…During the study, the natural regeneration of the sand deposit during large flood events was observed. It is possible to improve the system by replacing the artificial weirs with ramps of gabions 2 that maintain hydraulic continuity and produce more efficient aeration than waterfalls (Khdhiri 2014;Khdhiri et al 2014). Constructed riffles should be tested on other small creeks in parallel with a design assistance model.…”
Section: Discussionmentioning
confidence: 99%